2017
DOI: 10.1080/07357907.2017.1289216
|View full text |Cite
|
Sign up to set email alerts
|

CD40 Ligand Is Increased in Mast Cells in Psoriasis and Actinic Keratosis but Less So in Epithelial Skin Carcinomas

Abstract: The expression of CD40 ligand (CD40L) in mast cells was investigated in biopsies from lesional and non-lesional skin samples of patients with psoriasis, actinic keratosis (AK), basal cell carcinoma, and squamous cell carcinoma using a sequential double-staining technique. The percentage of CD40L mast cells was higher in the lesional than in the non-lesional skin (p < .003). Interestingly, this percentage was lower in both carcinomas than in psoriasis and actinic keratosis (p < .025). Cells immunopositive for C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…In line with this finding, about 60 % of patients with HS report moderate or severe pruritus (Matusiak et al, 2018). Similarly, more than one third of patients with basal cell carcinoma or squamous cell carcinoma report to have pruritus (Mills et al, 2012; Yosipovitch et al, 2014) and elevated mast cell numbers in both tumors have been reported (Diaconu et al, 2007; Haimakainen et al, 2017). The connection between mast cell numbers and itch is not so clear in melanoma, in which less patients report itch (Yosipovitch et al, 2014) and both increased (Toth-Jakatics et al, 2000; Ribatti et al, 2003a, b), and decreased (Biswas et al, 2014; Siiskonen et al, 2015; Rajabi et al, 2017) mast cell numbers have been reported.…”
Section: Mast Cells Skin Diseases and Itchmentioning
confidence: 99%
“…In line with this finding, about 60 % of patients with HS report moderate or severe pruritus (Matusiak et al, 2018). Similarly, more than one third of patients with basal cell carcinoma or squamous cell carcinoma report to have pruritus (Mills et al, 2012; Yosipovitch et al, 2014) and elevated mast cell numbers in both tumors have been reported (Diaconu et al, 2007; Haimakainen et al, 2017). The connection between mast cell numbers and itch is not so clear in melanoma, in which less patients report itch (Yosipovitch et al, 2014) and both increased (Toth-Jakatics et al, 2000; Ribatti et al, 2003a, b), and decreased (Biswas et al, 2014; Siiskonen et al, 2015; Rajabi et al, 2017) mast cell numbers have been reported.…”
Section: Mast Cells Skin Diseases and Itchmentioning
confidence: 99%
“…Their data demonstrated that CD40-CD40L cross-talk integrated strong antigenic signals and microbial stimuli to induce the development of IL-17-producing CD4 + T cells ( Iezzi et al, 2009 ). In psoriatic skin lesions, the number of CD40 + cells (keratinocytes, Langerhans cells, mature DCs) and CD40L + mast cells is higher than that in healthy skin ( Haimakainen et al, 2017 ). In patients with psoriatic arthritis (PsA), the expression of CD40 was increased in synovial fluid B cells (Armas-Gonzalez et al, 2015 ) and the expression of CD40L was significantly upregulated on activated T cells compared to healthy controls ( Daoussis et al, 2007 ).…”
Section: Co-stimulatory Moleculesmentioning
confidence: 99%
“…Recently, mast cells were reported to express vitamin D3 metabolising enzymes, CYP27A1 and CYP27B1, in skin SCC and BCC, suggesting a role in an immunosuppressive environment in skin cancers . In addition, the percentage of CD40 ligand‐positive MCs was found lower in lesional BCC and SCC compared to actinic keratosis and psoriasis, indicating a dysregulated immune response by mast cell CD40L in skin cancer …”
Section: The Role Of Mast Cells In Uv‐driven Diseasesmentioning
confidence: 99%